Probing charge transfer in benzodifuran-C60 dumbbell-type electron donor-acceptor conjugates: Ground- and excited-state assays - Li, Hui; Schubert, Christina; Dral, Pavlo; Costa, Ruben Dario; La Rosa, Andrea; Thüring, Jürg; Liu, Shi-Xia; Yi, Chenyi; Filippone, Salvatore; Martín, Nazario; Decurtins, Silvio; Clark, Timothy; et al. (ChemPhysChem, 2013)
Rigid electron donor-acceptor conjugates (1-3) that combine π-extended benzodifurans as electron donors and C molecules as electron acceptors with different linkers have been synthesized and investigated with respect to intramolecular charge-transfer events. Electrochemistry, fluorescence, and transient absorption measurements revealed tunable and structure-dependent charge-transfer processes in the ground and excited states. Our experimental findings are underpinned by density-functional theory calculations. Dumbbell arrays: A benzodifuran (BDF) donor is for the first time fused to two C molecules by different linkers to form triads 1-3 (see figure). Their redox behavior, absorption, fluorescence emission, and photoinduced intramolecular charge-transfer events have been investigated experimentally and theoretically. The lifetime of the resulting charge-separated state varies distinctly with the polarity of the solvents and the distance between the BDF and C units. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.